Electrolyte for preparing high-elongation lithium battery copper foil, copper foil and preparation method of copper foil

By adding specific additives to the electrolyte of lithium battery copper foil and adjusting the plating solution conditions, the problem that the elongation of lithium battery copper foil does not meet the target requirements is solved, and the lithium battery copper foil with high elongation and high tensile strength is achieved, which improves safety.

CN119640345APending Publication Date: 2025-03-18JIANGXI PROVINCE JIANGTONG YEZI COPPER FOIL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411788143.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the elongation rate of lithium battery copper foil does not meet the target requirements, which can easily cause safety problems such as short circuits.

Method used

An electrolyte for the preparation of high elongation lithium battery copper foil, including the main electrolyte and specific additives are used. The main electrolyte consists of copper sulfate, sulfuric acid and chloride ions, and the additives include amino-containing polymer compounds, compounds with sulfonic acid groups, polyepoxy compounds, etc. By adjusting the additive ratio and plating solution conditions, the microstructure structure of the copper foil is regulated.

Benefits of technology

Effectively regulate the microstructure structure of copper foil, obtain dense and uniform lithium battery copper foil, with high room temperature elongation and tensile strength, and reduce the occurrence of safety problems such as short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640345A_ABST
    Figure CN119640345A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte for preparing a high-elongation lithium battery copper foil, a copper foil and a preparation method of the copper foil, the electrolyte comprises a main electrolyte and additives, the main electrolyte comprises copper sulfate, sulfuric acid and chloride ions, the additives comprise a first additive with the concentration of 5-40 mg / L and a second additive with the concentration of 2-20 mg / L, the concentration of the first additive is 10-100 mg / L, the concentration of the second additive is 10-100 mg / L, the concentration of the third additive is 10-100 mg / L, the first additive is an amino-containing high-molecular compound, the concentration of the second additive is a compound with a sulfonic acid group, and the concentration of the third additive is a mixture of a polyepoxy compound, a modified polysaccharide compound and a polyamine compound. By adopting the additive in the scheme and the specific proportion thereof, the microstructure of the copper foil can be effectively regulated and controlled, the lithium battery copper foil with compact and uniform texture is obtained, and meanwhile, the lithium battery copper foil has high normal-temperature ductility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery copper foil preparation, and in particular to an electrolyte solution for preparing high-elongation lithium battery copper foil, a copper foil and a preparation method thereof. Background Art

[0002] Lithium battery copper foil is an important component of lithium-ion batteries and is used to carry the negative electrode active material layer.

[0003] In the prior art, a series of reactions occur inside lithium batteries during the charge and discharge process, which will cause the lithium battery copper foil to repeatedly expand and contract. If the elongation of the copper foil does not meet the target requirements, it is easy to cause safety problems such as short circuits. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an electrolyte, copper foil and a preparation method thereof for preparing high elongation lithium battery copper foil, aiming to solve the technical problem in the prior art that when the elongation of the copper foil does not meet the target requirements, it is easy to cause safety problems such as short circuit.

[0005] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides: an electrolyte for preparing high elongation lithium battery copper foil, comprising a main electrolyte and additives, the main electrolyte comprising copper sulfate, sulfuric acid and chloride ions, the additives comprising a first additive with a concentration of 5-40 mg / L, a second additive with a concentration of 2-20 mg / L, and a third additive with a concentration of 10-100 mg / L, the first additive is an amino-containing polymer compound, the second additive is a compound having a sulfonic acid group, and the third additive is a mixture of polyepoxide compounds, modified polysaccharide compounds, and polyamine compounds.

[0006] According to one aspect of the above technical solution, the first additive is one or more of polypeptide trimer helix, poly-natural amino acid, and hydrolyzed collagen.

[0007] According to one aspect of the above technical solution, the second additive is one or more of dimercaptopropanesulfonic acid sodium salt, sodium thiopropanesulfonate, and sodium dimethylformamidopropanesulfonate.

[0008] According to one aspect of the above technical solution, the third additive is one or more of chloroethanol-modified water-soluble cellulose, fatty amine ethylene oxide copolymer sulfonic acid sodium salt, homopolyethylene glycol, and trimethylpropylammonium hydroxide inner salt.

[0009] According to one aspect of the above technical solution, the concentration of copper sulfate is 80-92 g / L.

[0010] According to one aspect of the above technical solution, the concentration of the sulfuric acid is 110-130 g / L.

[0011] According to one aspect of the above technical solution, the concentration of chloride ions is 18-22 mg / L.

[0012] In a second aspect, the present invention provides a method for preparing a high-elongation lithium battery copper foil, the method comprising the following steps: placing the electrolyte described in the above technical solution into an electrolytic cell, and obtaining the copper foil by electrolysis.

[0013] According to one aspect of the above technical solution, the method further includes:

[0014] Bath conditions include: current density 60-76A / dm 2 , the electrolyte temperature is 50-55℃, and the copper foil specification is 6-12μm.

[0015] In a third aspect, the present invention provides a high-elongation lithium battery copper foil, which is prepared by the preparation method described in the above technical solution.

[0016] Compared with the prior art, the beneficial effect of the present invention is that by adopting the additives of the present scheme and their specific proportions, the microstructure of the copper foil can be effectively regulated to obtain a lithium battery copper foil with a dense and uniform structure and a high room-temperature elongation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an electron microscope image of the copper foil prepared by the electrolyte in the first embodiment of the present invention;

[0018] Figure 2 This is an electron microscope image of the copper foil prepared by the electrolyte in the second embodiment of the present invention;

[0019] Figure 3 This is an electron microscope image of a copper foil prepared by the electrolyte in the third embodiment of the present invention;

[0020] Figure 4 This is an electron microscope image of a copper foil prepared by the electrolyte in the fourth embodiment of the present invention;

[0021] Figure 5 This is an electron microscope image of a copper foil prepared by the electrolyte in the fifth embodiment of the present invention;

[0022] Figure 6 This is an electron microscope image of a copper foil prepared by the electrolyte in the sixth embodiment of the present invention;

[0023] Figure 7 This is an electron microscope image of a copper foil prepared by the electrolyte in the seventh embodiment of the present invention;

[0024] The following specific implementation manner will further illustrate the present invention in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0026] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0028] The first embodiment of the present invention provides an electrolyte for preparing a high-elongation lithium battery copper foil, including a main electrolyte and additives, wherein the main electrolyte includes copper sulfate, sulfuric acid and chloride ions, the additives include a first additive with a concentration of 5-40 mg / L, a second additive with a concentration of 2-20 mg / L, and a third additive with a concentration of 10-100 mg / L, the first additive is an amino-containing polymer compound, the second additive is a compound having a sulfonic acid group, and the third additive is a mixture of a polyepoxide compound, a modified polysaccharide compound, and a polyamine compound.

[0029] Specifically, the first additive is one or more of polypeptide trimeric helices, polynatural amino acids, and hydrolyzed collagen; wherein the concentration of polypeptide trimeric helices is 0.2-0.8 mg / L; the concentration of polynatural amino acids is 6-14 mg / L; the concentration of hydrolyzed collagen is 0.2-0.8 mg / L. Preferably, in this embodiment, the first additive is composed of polypeptide trimeric helices at a concentration of 0.5 mg / L, polynatural amino acids at a concentration of 10 mg / L, and hydrolyzed collagen at a concentration of 0.5 mg / L.

[0030] The second additive is one or more of dimercaptopropanesulfonic acid sodium salt, thioalkylpropanesulfonic acid sodium salt, and dimethylformamidopropanesulfonic acid sodium salt; wherein the concentration of dimercaptopropanesulfonic acid sodium salt is 2-6 mg / L; the concentration of thioalkylpropanesulfonic acid sodium salt is 0.2-0.8 mg / L; the concentration of dimethylformamidopropanesulfonic acid sodium salt is 0.2-0.8 mg / L. Preferably, in this embodiment, the second additive is dimercaptopropanesulfonic acid sodium salt with a concentration of 4 mg / L.

[0031] The third additive is one or more of chloroethanol-modified water-soluble cellulose, sodium salt of fatty amine ethylene oxide copolymer sulfonic acid, homopolyethylene glycol, and trimethyl propyl ammonium hydroxide inner salt; wherein the concentration of chloroethanol-modified water-soluble cellulose is 6-14 mg / L; the concentration of sodium salt of fatty amine ethylene oxide copolymer sulfonic acid is 6-14 mg / L; the concentration of homopolyethylene glycol is 1-4 mg / L, and the concentration of trimethyl propyl ammonium hydroxide is 0.2-0.8 mg / L. Preferably, in this embodiment, the third additive is composed of 10 mg / L of chloroethanol-modified water-soluble cellulose, 10 mg / L of sodium salt of fatty amine ethylene oxide copolymer sulfonic acid, and 2 mg / L of homopolyethylene glycol.

[0032] Specifically, the concentration of the copper sulfate is 80-92 g / L, and in this embodiment, the concentration of the copper sulfate is preferably 85 g / L. The concentration of the sulfuric acid is 110-130 g / L, and in this embodiment, the concentration of the sulfuric acid is preferably 125 g / L. The concentration of the chloride ion is 18-22 mg / L, and in this embodiment, the concentration of the chloride ion is preferably 20 g / L.

[0033] In this embodiment, based on the above electrolyte, the copper foil specification is 6 μm, the electrolyte temperature is 55° C., and the current density is 60 A / dm 2 The electron microscope morphology of the copper foil prepared under the plating solution conditions is shown in Figure 1 shown.

[0034] The second embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0035] The plating conditions include a copper foil size of 8 μm and a current density of 76 A / dm 2 .

[0036] The electron microscope morphology of the copper foil prepared under the above-mentioned plating conditions in this embodiment is shown in FIG. Figure 2 shown.

[0037] The third embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that of the first embodiment, except that:

[0038] The plating conditions include a copper foil size of 10 μm and a current density of 76 A / dm 2 .

[0039] The electron microscope morphology of the copper foil prepared under the above-mentioned plating conditions in this embodiment is shown in FIG. Figure 3 shown.

[0040] The fourth embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0041] The plating conditions include a copper foil size of 12 μm and a current density of 76 A / dm 2 .

[0042] The electron microscope morphology of the copper foil prepared under the above-mentioned plating conditions in this embodiment is shown in FIG. Figure 4 shown.

[0043] The fifth embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0044] The plating conditions include a copper foil size of 8 μm and a current density of 76 A / dm 2 ;

[0045] The third additive is composed of 12 mg / L chloroethanol-modified water-soluble cellulose, 12 mg / L fatty amine ethylene oxide copolymer sulfonic acid, and 2.4 mg / L homopolyethylene glycol.

[0046] The electron microscope morphology of the copper foil prepared under the above-mentioned plating conditions in this embodiment is shown in FIG. Figure 5 shown.

[0047] The sixth embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0048] The plating conditions include a copper foil size of 8 μm and a current density of 76 A / dm 2 ;

[0049] The second additive is composed of sodium dimercaptopropanesulfonate with a concentration of 4 mg / L, sodium thiohydrylpropanesulfonate with a concentration of 0.5 mg / L, and sodium dimethylformamidopropanesulfonate with a concentration of 0.5 mg / L.

[0050] The electron microscope morphology of the copper foil prepared under the above-mentioned plating conditions in this embodiment is shown in FIG. Figure 6 shown.

[0051] The seventh embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0052] The plating conditions include a copper foil size of 8 μm and a current density of 76 A / dm 2 ;

[0053] The second additive is composed of 4 mg / L sodium dimercaptopropanesulfonate, 0.5 mg / L sodium thioalcoholpropanesulfonate, and 0.5 mg / L sodium dimethylformamidopropanesulfonate;

[0054] The third additive is composed of 12 mg / L chloroethanol-modified water-soluble cellulose, 10 mg / L fatty amine ethylene oxide copolymer sulfonic acid, 2 mg / L homopolyethylene glycol, and 0.5 mg / L trimethylpropylammonium hydroxide inner salt.

[0055] The electron microscope morphology of the copper foil prepared under the above-mentioned plating conditions in this embodiment is shown in FIG. Figure 7 shown.

[0056] The electrolyte prepared in the above Examples 1-7 was subjected to copper plating treatment, and the plating conditions are shown in Table 1 below:

[0057]

[0058] Table 1

[0059] The prepared copper foil was subjected to room temperature tensile strength test, room temperature elongation test, rough surface Rz test and bright surface Ra test respectively;

[0060] Test standard:

[0061] Roughness test (Rz, ten-point roughness average) is carried out according to standard GB / T29847-2013, using German Mahr M300 roughness tester to test the roughness of the matte surface and the glossy surface.

[0062] The tensile strength and elongation test was conducted according to the standard GB / T29847-2013 using a Shimadzu AGS-X-10KN normal temperature tensile machine at room temperature (25°C).

[0063] The experimental results are shown in Table 2 below:

[0064]

[0065] Table 2

[0066] As shown in Table 2 above, the present invention can be used at 55°C and a current density of 60-76A / dm2 Under the conditions, a lithium battery copper foil with dense structure, low roughness, high tensile strength and elongation is prepared. Based on the above-mentioned electrolyte composition, additive ratio and physical conditions of the plating solution, a high elongation lithium battery copper foil that meets the requirements can be obtained.

[0067] In summary, through the above-mentioned technical scheme of the present invention, the above-mentioned additives and their specific proportions are used to effectively regulate the microstructure of the copper foil, control the grain growth, and obtain a dense lithium battery copper foil, which is suitable for the production of high elongation lithium battery copper foil with a thickness of 6-12μm. The lithium battery copper foil prepared in this way has high tensile strength and high elongation at room temperature, and the foil surface is glossy without obvious appearance defects.

[0068] The eighth embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0069] The first additive is composed of a polypeptide trimeric helix with a concentration of 0.2 mg / L, polynatural amino acids with a concentration of 6 mg / L, and hydrolyzed collagen with a concentration of 0.2 mg / L.

[0070] The second additive is composed of sodium dimercaptopropanesulfonate with a concentration of 2 mg / L, sodium thiohydrylpropanesulfonate with a concentration of 0.2 mg / L, and sodium dimethylformamidopropanesulfonate with a concentration of 0.2 mg / L.

[0071] The third additive is composed of 6 mg / L chloroethanol-modified water-soluble cellulose, 6 mg / L sodium salt of fatty amine ethylene oxide copolymer sulfonate, 1 mg / L homopolyethylene glycol, and 0.2 mg / L trimethylpropylammonium hydroxide.

[0072] The concentration of the copper sulfate is 80 g / L, the concentration of the sulfuric acid is 110 g / L, and the concentration of the chloride ion is 18 mg / L.

[0073] The ninth embodiment of the present invention provides an electrolyte for preparing a high elongation lithium copper foil. The proportion of the electrolyte is basically the same as that in the first embodiment, except that:

[0074] The first additive is composed of a polypeptide trimeric helix with a concentration of 0.8 mg / L, polynatural amino acids with a concentration of 14 mg / L, and hydrolyzed collagen with a concentration of 0.8 mg / L.

[0075] The second additive is composed of sodium dimercaptopropanesulfonate with a concentration of 6 mg / L, sodium thiohydrylpropanesulfonate with a concentration of 0.8 mg / L, and sodium dimethylformamidopropanesulfonate with a concentration of 0.8 mg / L.

[0076] The third additive is composed of 14 mg / L chloroethanol-modified water-soluble cellulose, 14 mg / L sodium salt of fatty amine ethylene oxide copolymer sulfonate, 4 mg / L homopolyethylene glycol, and 0.8 mg / L trimethylpropylammonium hydroxide.

[0077] The concentration of the copper sulfate is 92 g / L, the concentration of the sulfuric acid is 130 g / L, and the concentration of the chloride ion is 22 mg / L.

[0078] The ninth embodiment of the present invention provides a method for preparing a high-elongation lithium battery copper foil, the method comprising the following steps: placing the electrolyte described in the above embodiment into an electrolytic cell, and obtaining the copper foil by electrolysis.

[0079] In this embodiment, the above method further includes: controlling the plating solution conditions including: the current density is 60-76A / dm 2 , the electrolyte temperature is 50-55°C, and the copper foil specification is 6-12 μm. In this embodiment, the electrolyte temperature is preferably 50°C.

[0080] The tenth embodiment of the present invention provides a high-elongation lithium battery copper foil, which is prepared by the preparation method described in the above embodiment.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0082] The above-described embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. An electrolyte for preparing high elongation lithium copper foil, characterized in that: It includes a main electrolyte and additives, the main electrolyte includes copper sulfate, sulfuric acid and chloride ions, the additives include a first additive with a concentration of 5-40 mg / L, a second additive with a concentration of 2-20 mg / L, and a third additive with a concentration of 10-100 mg / L, the first additive is an amino-containing polymer compound, the second additive is a compound with a sulfonic acid group, and the third additive is a mixture of a polyepoxide compound, a modified polysaccharide compound, and a polyamine compound.

2. The electrolyte for preparing high elongation lithium copper foil according to claim 1, characterized in that: The first additive is one or more of polypeptide trimer helix, poly natural amino acid, and hydrolyzed collagen.

3. The electrolyte for preparing high elongation lithium battery copper foil according to claim 1, characterized in that: The second additive is one or more of dimercaptopropanesulfonic acid sodium salt, sodium thiohydrylpropanesulfonate, and sodium dimethylformamidopropanesulfonate.

4. The electrolyte for preparing high elongation lithium copper foil according to claim 1, characterized in that: The third additive is one or more of chloroethanol-modified water-soluble cellulose, sodium salt of fatty amine ethylene oxide copolymer sulfonate, homopolyethylene glycol, and trimethylpropylammonium hydroxide inner salt.

5. The electrolyte for preparing high elongation lithium battery copper foil according to claim 1, characterized in that: The concentration of the copper sulfate is 80-92 g / L.

6. The electrolyte for preparing high elongation lithium battery copper foil according to claim 1, characterized in that: The concentration of the sulfuric acid is 110-130 g / L.

7. The electrolyte for preparing high elongation lithium copper foil according to claim 1, characterized in that: The concentration of the chloride ions is 18-22 mg / L.

8. A method for preparing a high elongation lithium battery copper foil, characterized in that: The method comprises the following steps: placing the electrolyte described in any one of claims 1 to 7 into an electrolytic cell, and obtaining copper foil through electrolysis.

9. The method for preparing a high elongation lithium battery copper foil according to claim 8, characterized in that: The method further comprises: Bath conditions include: current density 60-76A / dm 2 , the electrolyte temperature is 50-55℃, and the copper foil specification is 6-12μm.

10. A high elongation lithium battery copper foil, characterized in that: The copper foil is prepared by the preparation method described in claim 8 or 9.